Mutagenic Improvement of Xylanase Production from Xylanolytic Bacteria and its Phylogenetic Analysis - CHUSNUL HANIM; LIES MIRA YUSIATI; MUHAMMAD NUR CAHYANTO; ALI WIBOWO (Indonesian Society for microbiology, 2013)
This study was conducted to obtain xylanolytic mutants that have higher xylanase activity than their wildtype counterparts. A mutant with the best xylanolytic activity was selected and identified based on its 16S rRNA sequence. Its optimum growth condition was also characterized and its phylogenetic relations to other xylanolytic bacteria were analzsed. Wild type xylanolytic alkalophlic bacteria were grown in medium containing xylan as a substrate. Mutation was performed using ethidium bromide (EtBr) or ethyl methanesulfonate (EMS) atconcentrations 50, 100, and 150 mg mL-1 and times of exposure 30, 60, 90, and 120 min for each treatment. Twenty two mutants were obtained from EtBr and 24 mutants from EMS mutageneses. The mutants were analyzed for their capability to secrete xylanase into xylan medium containing xylose or glucose or glycerol. Growth optimizations of the mutant were done in media with pH range 6-11 and temperature range 30 to 60 °C. Mutant number 19, which was obtained by treatment using 50 mg mL-1 EMS for 120 min, had the highest xylanase activity (15.057 U g-1). This activity was obtained at optimum growth conditions: pH 9.5 and temperature 55 °C. Chromosomal DNA of this mutant was extracted and amplified by PCR using 16S rRNA gene specific primers. The amplified fragments were sequenced by dideoxynucleotide chain terminator method. The phylogenetic analysis based on 16S rRNA gene sequence showed that mutant 19 was closed to an anaerobic xylanase producing bacteria.